Manually operated onions grading machine for the agricultural product / Intan Nur Mawaddah Mohd Shah, Kamariah Md Isa and Ab Aziz Mohd Yusof - Mohd Shah, Intan Nur Mawaddah; Isa, Kamariah Md; Mohd Yusof, Ab Aziz (School of Mechanical Engineering, 2023)
Onion grades are determined by various onion sizes. The method of isolating onion size nowadays is quite complicated as it requires a lot of manpower at the same time. This will take more time to isolate the onions. So, this project will help more parties by reducing segregation time and a large amount of manpower. This project requires only a small amount of manpower and is carried out manually only. The method of using this machine is, the user has to insert the onion into the roller and turn the lever on the side of the machine. The onion will fall down according to the size available on the loop. At the end of the process, many onions can be separated into the desired grade based on their size in a short time in large quantities. The target market for this project is a small-scale industry.